Pricing and green promotion decisions in a retailer-owned dual-channel supply chain with multiple manufacturers - Yaping Zhao; Wenjie Huang; Endong Xu; Xiaoyun Xu (Cleaner Logistics and Supply Chain)
This paper studies the pricing and green promotion effort decisions in a retailer-owned dual-channel supply chain consisting of multiple manufacturers and one retailer. Specifically, we consider the general version of the problem where multiple inter-correlated products are sold through both the online and the offline retail channels, and customer demands are jointly affected by product retail prices and green promotion efforts. With the objective of maximizing the members’ profits, game theoretic models are built to obtain the optimal decisions on wholesale prices, retail price markups and green promotion efforts under different power structures including manufacturer-Stackelberg, retailer-Stackelberg, Nash and integrated power structures. For several important special cases, explicit analytical relationships among optimal decisions and corresponding profits are established. For the more general settings, extensive numerical experiments are conducted to compare the system performance across different power structures. Our results indicate that the individual and overall profits are primarily driven by demand sensitivity to retail price. An increase in demand sensitivity will result in higher profits for all members at equilibrium. Our research also indicates that, regardless of power structures, the overall profit can also be driven up by increased product variety. For greening promotion efforts, the research reveals that the increase in the costs will have greater impactson the profit of the retailer than the manufacturers. Finally, our results demonstrate that being a Stackelberg leader is always advantageous if the objective is to optimize one’s individual profit,. But the significance of such an advantage is affected by the product independence. This paper extends the scope of existing studies by considering multiple correlated products in retailer-owned dual-channel supply chains, and rationalizes members’ pricing and green promotion effort decisions under competition.